Effect of heterocycles on field-effect transistor performances of donor-acceptor-donor type small molecules - Chini, Mrinmoy Kumar; Mahale, Rajashree Y.; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
Two D-A-D small molecules comprising triphenylamine and diketopyrrolopyrrole were synthesized having either furan or thiophene connected to the fused lactam ring. In this design, furan/thiophene diketopyrrolopyrrole acts as an acceptor and triphenylamine acts as a donor. Propeller shaped triphenylamine has its effect on packing, processability and plays a vital role in determining the pi-pi molecular orbital stacking in such compounds and thus the mobility of charge carriers. With TDPPT and FDPPT, maximum hole carrier mobility obtained is 2.88 x 10(-3) cm(2) V-1 s(-1) and 1.60 x 10(-3) cm(2) V-1 s(-1), respectively using bottom gate bottom contact field-effect transistor. (C) 2016 Elsevier B.V. All rights reserved.